Sex, Age, and Ethnic Background Shape Adaptive Immune Responses Induced by the SARS-CoV-2 mRNA Vaccine - Bai, Jie; Chiba, Asako; Murayama, Goh; Kuga, Taiga; Tamura, Naoto; Miyake, Sachiko (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccine-induced adaptive responses have been well investigated. However, the effects of sex, age, and ethnic background on the immune responses elicited by the mRNA vaccine remain unclear. Here, we performed comprehensive analyses of adaptive immune responses elicited by the SARS-CoV-2 mRNA vaccine. Vaccine-induced antibody and T cell responses declined over time but persisted after 3 months, and switched memory B cells were even increased. Spike-specific CD4+ T and CD8+ T cell responses were decreased against the B.1.351 variant, but not against B.1.1.7. Interestingly, T cell reactivity against B.1.617.1 and B.1.617.2 variants was decreased in individuals carrying HLA-A24, suggesting adaptive immune responses against variants are influenced by different HLA haplotypes. T follicular helper cell responses declined with increasing age in both sexes, but age-related decreases in antibody levels were observed only in males, and this was associated with the decline of T peripheral helper cell responses. In contrast, vaccine-induced CD8+ T cell responses were enhanced in older males. Taken together, these findings highlight that significant differences in the reactogenicity of the adaptive immune system elicited by mRNA vaccine were related to factors including sex, age, and ethnic background.